(untitled) (Experimental biology, 2024)
Examining the evolutionary mechanisms driving genetic variation, alongside the global epidemiological landscape, provides insights into transmission patterns, seasonal outbreaks, and pandemic potential. This review explores the complex interplay between influenza virus genetic diversity and epidemiological dynamics within human populations. Insights gained from this synthesis inform public health strategies, emphasizing the importance of surveillance, vaccination, and pandemic preparedness to mitigate the impact of influenza. Influenza viruses exhibit significant genetic variation due to mechanisms such as antigenic drift and shift, as well as their segmented genome. New strains evolve through genetic alterations, enabling them to overcome existing immunity and spread both seasonally and globally. Understanding genetic diversity is essential for predicting strain evolution and developing effective vaccines. Influenza, a highly contagious respiratory virus, spreads via respiratory droplets. It affects individuals of all ages, but those at increased risk for severe disease include the elderly, young children, pregnant women, and individuals with underlying medical conditions. Influenza follows seasonal trends, with higher transmission rates in colder months in temperate regions, while tropical regions may experience year-round circulation. Epidemiological factors influencing influenza transmission and outcomes include population density, travel behavior, and healthcare infrastructure. Monitoring influenza’s epidemiological dynamics and examining genetic variants are critical tasks for surveillance systems. Effective control of influenza requires integrated strategies that address both genetic and epidemiological aspects. Controlling influenza epidemics, especially during a pandemic, involves using antiviral medications, early detection, and containment measures.